PENETAPAN SILIKON SECARA SPEKTROFOTOMETRI SEBAGAI KOMPLEKS HETEROPOLI BIRU MOLIBDENUM - Asmawati
Traces of silicon has been analyzed by spectrophotoaetry as molybdenum blue. The first step is the formation of the silicomolybdic acid complex with excess of ammonium molybdate reagent at pH 1,2-2,0. The yellow complex of silicomolybdic acid can be reduced with metol to the molybdenum blue complex. Then the absorbance of blue complex is measured at a maximum wavelength of 810 nm, that would have a greater sensitivity. The aim of this experiment is to give more information about the silicon analysis by spectrophotometry as molybdenum blue. The interference of small amounts of phosphorus can be eliminated by the addition of oxalic acid. On the other hand, a strong acid like sulfuric acid can destroy the phosphomolybdate complex, and suppresses the interferences of phosphorus by the time metol reduce the silicomolybdic acid. Application of this method is used for the determination of silicon content of mineralized drinking water samples produced by three companies with initials A, and C. The results of this analysis showed that the concentration of silicon in these samples were (36.57±0.25), (38.99±0.25), and (36.60±0.23) ppm respectively.